Locus of control and mothers' return to employment - Eva M. Berger; Luke Haywood (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper investigates the effect of locus of control (LOC) on the length of mothers' employment break after childbirth. Using data from the German Socio-Economic Panel Study (SOEP), duration data reveals that women with an internal LOC return to employment more quickly than women with an external LOC.We find that this effect is particularly pronounced in jobs in which the penalties in terms of lower wage growth are highest. We thus argue that the effect of LOC on return is mainly related to differential appreciation of the career costs of longer maternity leave.
Keywords: J22; J24; 330; Locus of Control; Noncognitive Skills; Personality; Maternal Employment; Female Labor Supply; Survival Analysis